ANALISIS LAPISAN BAWAH PERMUKAAN MENGGUNAKAN METODE GROUND PENETRATING RADAR PADA SUBGRADE YANG DIINJEKSI AIR SEMEN - Situngkir, Edwin Mehator; Rendy Satria, Trihanyndio; Asih Aryani Soemitro, Ria; Ferdian, Vidi (Direktorat Bina Teknik Jalan dan Jembatan, 2023)
Early road damage was caused, among other things, by high daily traffic (ADT), vehicles with excessive dimensions and load (ODOL) passing through, and problematic and soft ground conditions. Subgrade repairs can be carried out to overcome damage by applying the water-cement grouting method. To analyze the state of the subsurface layer after cement water was injected, a field test was carried out using Ground Penetrating Radar (GPR) data acquisition. The results of GPR data analysis on Sta 34+700 and Sta 37+850 on the Tuban–Babat–Lamongan–Gresik national road have shown that on the radargram, the grouting materials rise due to back pressure. The materials cannot penetrate the subgrade layer so that the grouting material spreads over the aggregate layer and comes out through the grouting holes at other points on the asphalt surface. In the radargram, the reflector can be seen as a small, sharp and uniform horizon along the trace to the bottom layer so that there is no change in the condition of the subgrade layer after water cement grouting. From this research, soil improvement using cement water injection in cohesive soil types does not significantly increase soil density because the injected cement water does not enter the soil micropores. Key words: grouting water cement, subsurface layer, subgrade, ground penetrating radar, radargram, reflector